(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The principles of calculating the temperature and pressure in the working chambers of the rotary vane engine with an external supply of heat are considered. The mathematical model for calculating the pressure and the temperature in the chamber with heat transfer between the working fluid and the chamber walls is built. The plots of the dependence of the pressure and the temperature in the chamber on the angle of rotation of the output shaft at the minimum and maximum temperature of the walls are obtained.